2008
DOI: 10.1007/s00441-008-0608-6
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression of pigment-epithelium-derived factor in rat cochlea

Abstract: Pigment-epithelium-derived factor (PEDF) is a 50-kDa glycoprotein with well-recognised expression in various mammalian organs showing diverse (e.g. anti-angiogenic and neuroprotective) activities. However, at present, no information is available regarding the potential function of this cytokine in the inner ear. As a first approach to investigating whether PEDF is involved in cochlear function, we have explored its protein expression in the rat cochlea by immunocytochemistry. Our results show that PEDF express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Next we examined the mechanism by which PVM/Ms the affect expression of junction proteins. PEDF is a 50-kDa glycoprotein previously found expressed in the rat inner ear, including in the SV (25). In this study, we found that PEDF is expressed in primary cultured PVM/Ms (Fig.…”
Section: Pvms Control Barrier Permeability By Affecting Global Expressupporting
confidence: 62%
“…Next we examined the mechanism by which PVM/Ms the affect expression of junction proteins. PEDF is a 50-kDa glycoprotein previously found expressed in the rat inner ear, including in the SV (25). In this study, we found that PEDF is expressed in primary cultured PVM/Ms (Fig.…”
Section: Pvms Control Barrier Permeability By Affecting Global Expressupporting
confidence: 62%
“…IHCs, OHCs, and Deiters cells were also PEDF-positive after 120 min. PEDF was not detected in the basilar membrane in guinea pigs, which has been reported in rats (Gleich and Piña, 2008 ). PEDF gene expression was further analyzed using RNAscope in the cochleae of normal guinea pigs and we found mRNA transcripts in spiral ganglion type 1 neurons, type I and type II fibrocytes, marginal cells, and basal cells of the stria vascularis.…”
Section: Discussionmentioning
confidence: 50%
“…It is also reported to have regulating functions in osteogenesis, to promote stem cell renewal and inhibit tumor angiogenesis (Brook et al, 2020 ). PEDF has been identified in the stria vascularis, spiral ganglion, neurons, and basilar membrane in the rat inner ear (Gleich and Piña, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic PEDF was shown to improve the EP and hearing thresholds. But PEDF is also found in the organ of Corti (Gleich and Piña, 2008 ) where it may also exert trophic effects. Notably, the mouse strain, age, and type of exposure used in these studies have been shown to produce massive disruption of the organ of Corti (Ohlemiller et al, 2018 ), and strial changes were likely not the major drivers of hearing loss.…”
Section: Strial Barrier Dysfunction Following Noise Exposurementioning
confidence: 99%